THE EFFECTIVENESS OF ACUPUNCTURE ON WOMEN WITH POLYCYSTIC OVARY SYNDROME: SYSTEMATIC LITERATURE REVIEW - Andriana Andriana; Sri Sumarni (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Women with polycystic ovary syndrome (PCOS) experience metabolic disorders and hyperandrogenism. The acupuncture is an alternative medicinal treatment and complimentary for the women with PCOS. The aim of this research was to identify acupuncture effectiveness for metabolism problem and hyperandrogenism for the women with PCOS. Methods: This was a systematic review using several published literature obtained from direct electronic data of science, PubMed, and other sites through the PRISMA method using the Boolean operator's system (AND). The inclusion criteria consisted of the studies with Randomized controlled trial (RCT) published in 2009 to 2019, women with PCOS aged 18 to 45 years old as the subjects, the intervention using all of the kind of acupuncture that was compared to placebo, physical training, sham,and medicines. Meanwhile, exclusion criteria were studies with systematic review and meta-analysis, focusing on intervention, medicines, and physical training by using experimental animals. The measurement value of HOMA-IR, LH, FSH, ratio LH/FSH, TT, FT, SHBG, and DHEA-S. Results: The search resulted in 509 studies, of which a total of 6 studies were included in this systematic review. The acupuncture has effects on metabolism problem and hyperandrogenism for the women with PCOS, such as the decrease of HOMA-IR (3 studies) and LH tense (2 studies), LH/FSH ratio reduction (3 studies), as well as, the decline of TT tense (4 studies) and FT tense (4 studies), but the increase of SHBG tense (3 studies), and the decrease of DHEA-S (2 studies). However, the tense of LH had nosignificant change in all of the studies. Conclusions: The acupuncture can be effective in solving the metabolism problem and hyperandrogenism of women with PCOS. Keywords: Acupuncture, Polycystic Ovary Syndrome (PCOS), Hormone, Alternative medicinal treatment